Cardiac surgeryA simple heart valve replacement technique which improves surgical time - Emrecan, Bilgin; Özcan, Ali Vefa; Özdemir, Ahmet Coşkun (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Aim of the study : Different heart valve replacement techniques have been described in the literature. In the present study, a simple and very fast heart valve replacement technique is presented. Material and methods : In a two-year period, 87 patients with the diagnosis of mitral valve disease, aortic valve disease or combined valve disease underwent valve replacement performed by the same surgeon. In this technique, the valve was implanted with the valve clamped to the surgical dressing without the assistant holding it. Patients with coexisting surgical pathologies were excluded from the study. A control group was created among the patients who were operated on during the same time period by different surgeons with the assistant holding the prosthesis. Control group operations were done by conventional valve holding and suturing techniques. Results : Mean age of the patients was 61.6 ±3.2 years. Mitral valve replacement (MVR) was done to 51 patients, aortic valve replacement (AVR) to 12 patients and both aortic and MVR to 24 patients. Aortic cross clamp duration was 30.7 ±3.3 min for MVR, 34.8 ±6.2 min for AVR and 69.1 ±6.1 min for both valve replacements. Aortic clamping durations were significantly higher in the conventional implantation technique. Discussion: The described technique has many advantages such as short myocardial ischemia duration, better exposure of the surgical field and facilitation of assistance.